Save LIVES technical package: 22 interventions that could make a difference - Peden, M; Khayesi, M (BMJ Publishing Group, 2018)
The Save LIVES: a road safety technical package was produced and launched in May 2017 by the WHO to support road safety decision makers and practitioners in their efforts to significantly reduce the number of road traffic deaths in their countries. This Special Feature explains the process used to develop the package and how and why the 22 interventions were included. It concludes by encouraging researchers and practitioners to tailor their road safety packages to their own realities by following five practical steps.